Solvent‐Mediated Structural Evolution in Colloidal Lead Halide Perovskite Nanocrystals Self‐Assembly (Adv. Mater. Interfaces 19/2022). Issue 19 (4th July 2022) - Chen, Linqi; Hu, Yingjie; Zhou, Beier; Dong, Hongxing; Mou, Nanli; He, Jin; Yang, Zhijie; Li, Jingzhou; Zhu, Zihao; Zhang, Long
Abstract : Solvent‐Mediated Evolution of Colloidal Lead Halide Perovskite Nanocrystals In article number 2200187, Linqi Chen, Hongxing Dong, Long Zhang, and co‐workers demonstrate a molecular scale mechanism of solvent‐mediated evolution of all‐inorganic lead halide perovskite nanocrystals (NCs). By affecting the intermolecular forces between aliphatic ligands on adjacent NCs and regulating the competition between complex bond energy in colloidal NCs system, solvent molecules regulate the self‐assembly of ligand‐stabilized perovskite NCs and NC arrays and nanowires are freely obtained.